Implemetation of Horisontal Net in Seaweed (Kappahycus alvarezii and Eucheuma denticulatum) Cultivation - Balubi, Abdul Muis; Mustafa, Ahmad; Muzuni, Muzuni; Jalil, Wardha; Kasim, Ma’ruf (Universitas Halu Oleo, 2019)
Cultivation of seaweed genus Eucheuma continues to develop with various methods in increasing of production. This research was conducted during March-July at the Lakeba Beach, Baubau City, Southeast Sulawesi Province. Indonesia. The results showed that the growth rate of Eucheuma denticulatum and Kappaphycus alvarezii in floating cages looked faster and there was a better morphological form of talus. The average production of E. denticulatum which uses floating cages and longline in 50 g for first day cultivation is growth to 74 g and 60 g, respectively. The absolute growth rate of the thallus E. denticulatum during July cultivated with floating cages and longline after 30 days from the average initial weight of 50 g growth to 240 g and 167 g, respectively. Specific Growth Rate (SGR) of E. denticulatum cultivated on longline looks lower compared to floating cages. SGR of K. alvarezii and E. denticulatum which are cultivated by floating cage are 5,6%/day and 5,4% /day respectively. Cultivation using floating cages produces good growth rates without the effects of herbivorous attacks.Keywords: ; Eucheuma denticulatum, Herbivorous, Horintoal Net, Kappaphycus alvarezi, seaweed.